Analysis of oncological diseases in the Subcarpathian Oncology Center in 2007 - 2011 - Maciej Kochman; Katarzyna Niemiec; Helena Bartyzel-Lechforowicz; Mirosław Jabłoński (Kazimierz Wielki University, 2018)
Introduction: Cancers are a growing health, social and economic problem of society worldwide. They are the second cause of mortality in Poland, causing 27% of deaths among men and about 24% of deaths among women. For several decades, there has been a steady increase in morbidity and mortality due to malignant tumors. The increase in morbidity of oncological diseases is related to aging of the population and increasing exposure to carcinogens such as poor diet, alcohol consumption and smoking, stress, environmental pollution as well as genetic inheritance. Data of morbidity and mortality caused by cancers in Poland has been published by Oncology Center in Warsaw since 1979. Aim of the study: to analyze selected oncological diseases of patients of the Subcarpathian Oncology Center in Brzozów, Poland in 2007-2011 as well as to compare them with data based on national oncology statistics in Poland. Material and methods: the material were records of selected oncological diseases of 10520 patients (6053 women and 4467 men; aged 2 - 98) of the Subcarpathian Oncological Center in Brzozów, Poland in 2007-2011. Results: The highest morbidity occurred in the group aged 40 - 59, the lowest in the group aged 90 - 100. The greatest morbidity rate was noted for breast cancer and the lowest morbidity rate was noted for cervical cancer. Conclusion: The cervical cancer morbidity decreases and it may be the evidence of the raising awareness, prevention and complex medical diagnostics. Morbidity rate for skin cancer increases therefore it is necessary to implement programs related to the prevention of this cancer.